Preliminary study of light yield dependence on LAB liquid scintillator composition - 叶星辰 俞伯祥 周详 赵力 丁雅韵 刘梦超 丁雪峰 张烜 揭泉林 周莉 方建 陈海涛 胡维 牛顺利 颜嘉庆 赵航 洪道金 (Chinese physics C, 2015)
Liquid scintillator （LS） will be adopted as the detector material in JUNO （Jiangmen Underground Neutrino Observatory）. The energy resolution requirement of JUNO is 3%, which has never previously been reached. To achieve this energy resolution, the light yield of liquid scintillator is an important factor. PPO （the fluor） and bis-MSB （the wavelength shifter） are the two main materials dissolved in LAB. To study the influence of these two materials on the transmission of scintillation photons in LS, 25 and 12 cm-long quartz vessels were used in a light yield experiment. LS samples with different concentration of PPO and bis-MSB were tested. At these lengths, the light yield growth is not obvious when the concentration of PPO is higher than 4 g/L. The influence from bis-MSB becomes insignificant when its concentration is higher than 8 mg/L. This result could provide some useful suggestions for the JUNO LS.